PENGETAHUAN IBU TENTANG PERAWATAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITA 1 â 3 TAHUN DI PUSKESMAS MOJOSARI - Dwi w, Binarti (JURNAL KEPERAWATAN SEHAT, 2011)
ABSTRACTAcute respiratory infections (ARI), is an acute infectious process which lasted for 14 days. it is caused by microorganisms that attack one or more of the organ began and nasal airway (upper line) to the alveoli (lower line), including adbeksinya networks, such as the sinuses, middle ear cavity and the pleura.The research objective was to determine an overview of maternal knowledge about treatment of acute respiratory infections in toddlers years in community health centers Mojosari. sampling using consecutive sampling technique, a sample size of 20 respondents. Instruments and techniques of research used questionnaires filling out the questionnaire with the answers already available (closed questions) directly to the respondent. Knowledge criteria are grouped into three criteria, namely good, simply, lacking. The study found that half of respondents (50%) have sufficient knowledge about the treatment of acute respiratory tract infections in toddlers years Mojosari health centers. The results showed that maternal knowledge about the treatment of acute respiratory tract infections in toddlers years of knowledge deemed sufficient.Keywords: Knowledge, Acute Respiratory Infection,Toddler